2005
DOI: 10.1007/s10354-005-0191-3
|View full text |Cite
|
Sign up to set email alerts
|

Driving after cerebral ischemia – a driving simulator investigation

Abstract: All patients had only mild deficits and stated themselves able to drive. We could demonstrate the need to focus on driving skills especially in patients with MCA-infarctions. The driving simulator assesses various physical and neuropsychological functions influencing driving. It may especially be used for expert opinions regarding driving licence. It can also serve as a pre-driver evaluation before on road driving tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…During the City Driving Scenario, patients made over twice as many errors as the control participants. This finding is supported by the results of previous driving simulator studies that investigated the performance of patients 7-14 days [24] and at least three months [25] post-stroke. The findings of the current study are also consistent with the results of Schweizer and colleagues [9], which showed that increased recruitment of various brain networks was required when driving situations increased in complexity.…”
Section: Discussionsupporting
confidence: 88%
“…During the City Driving Scenario, patients made over twice as many errors as the control participants. This finding is supported by the results of previous driving simulator studies that investigated the performance of patients 7-14 days [24] and at least three months [25] post-stroke. The findings of the current study are also consistent with the results of Schweizer and colleagues [9], which showed that increased recruitment of various brain networks was required when driving situations increased in complexity.…”
Section: Discussionsupporting
confidence: 88%
“…Few reports have examined the driving abilities of patients with stroke using a driving simulator. Studies have shown that patients with stroke tend to perform worse on driving simulators than healthy individuals; however, this association was not observed with regard to road driving (9,11). The driving simulator used in the present study enables the evaluation of the course of travel and reactions and steering wheel operation.…”
Section: █ Conclusionmentioning
confidence: 83%
“…Clearly, it is important to caution those unable to drive safely against driving. Stroke can be a risk factor for decreased driving safety, as evidenced by increased “crash” rates on driving simulators [37] and a greater likelihood of at‐fault automobile crashes among stroke survivors aged 65 years or older [38].…”
Section: Resultsmentioning
confidence: 99%